AL-KAFA’AH FI AL-NIKAH - Najmah Sayuti (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Kafa'ah in marriage is basically equality, suitability and proportionality between the prospective couples getting married. Humans are required to kafa'ah in religion and religiosity. Non-Muslims can't kafa'ah with Muslims because of inequalities in beliefe. Some kafa'ah that should be considered in marriage is nasab, religion, belief or religiosity, profession, liberty and property.